Interindividual Variability of Lower-Limb Motor Cortical Plasticity Induced by Theta Burst Stimulation - Katagiri, Natsuki; Yoshida, Shinya; Koseki, Tadaki; Kudo, Daisuke; Namba, Shigehiro; Tanabe, Shigeo; Huang, Ying-Zu; Yamaguchi, Tomofumi (Frontiers in Neuroscience, 2020)
Theta burst stimulation (TBS) has been used as a tool to induce synaptic plasticity and improve neurological disorders. However, there is high interindividual variability in the magnitude of the plastic changes observed after TBS, which hinders its clinical applications. The electric field induced by transcranial magnetic stimulation (TMS) is strongly affected by the depth of the stimulated brain region. Therefore, it is possible that the variability in the response to TBS over the lower-limb motor cortex is different for the hand area. This study investigated the variability of TBS-induced synaptic plasticity in the lower-limb motor cortex, for intermittent TBS (iTBS), continuous TBS (cTBS), and sham iTBS, in 48 healthy young participants. The motor cortical and intracortical excitability of the tibialis anterior was tested before and after TBS using TMS. The results showed that iTBS had facilitatory effects on motor cortex excitability and intracortical inhibition, whereas cTBS exerted opposite effects. Twenty-seven percent of individuals exhibited enhanced motor cortical plasticity after iTBS, whereas 63% of participants showed enhanced plasticity after cTBS. In addition, the amount of TBS-induced plasticity was correlated with the intracortical excitability and the variability of the motor evoked potential prior to TBS. Our study demonstrated the high variability of the iTBS-induced lower-limb motor cortical plasticity, which was affected by the sensitivity of intracortical interneuronal circuits. These findings provide further insights into the variation of the response to TBS according to the anatomy of the stimulated brain region and the excitability of the intracortical circuit.